2016
DOI: 10.3390/molecules21050660
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Strategies for 5- and 6-Membered Ring Azaheterocycles Facilitated by Iminyl Radicals

Abstract: Abstract:The totality of chemical space is so immense that only a small fraction can ever be explored. Computational searching has indicated that bioactivity is associated with a comparatively small number of ring-containing structures. Pyrrole, indole, pyridine, quinoline, quinazoline and related 6-membered ring-containing aza-arenes figure prominently. This review focuses on the search for fast, efficient and environmentally friendly preparative methods for these rings with specific emphasis on iminyl radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 161 publications
0
19
0
Order By: Relevance
“…Recently, radical‐mediated C−N bond construction has gained traction because the relatively high reactivity of the open‐shell species provides opportunities for the development of transformations that are difficult using the two‐electron manifold . In this context, many research groups have employed the easily available oximes and their derivatives as radical precursors in radical C−N coupling reactions . The cleavage of the O−H bond in oxime produces a σ‐type iminoxyl radical with both a reactive oxygen and nitrogen atom .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, radical‐mediated C−N bond construction has gained traction because the relatively high reactivity of the open‐shell species provides opportunities for the development of transformations that are difficult using the two‐electron manifold . In this context, many research groups have employed the easily available oximes and their derivatives as radical precursors in radical C−N coupling reactions . The cleavage of the O−H bond in oxime produces a σ‐type iminoxyl radical with both a reactive oxygen and nitrogen atom .…”
Section: Methodsmentioning
confidence: 99%
“…[2] In this context, many research groups have employed the easily available oximes and their derivatives as radical precursors in radical CÀN coupling reactions. [3] Thecleavage of the OÀHbond in oxime produces a s-type iminoxyl radical with both ar eactive oxygen and nitrogen atom. [4] Han and co-workers have demonstrated that iminoxyl radicals can cyclize with alkenes or alkynes to form 5-membered N-heterocyclic compounds (Scheme 1a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, iminyl radical has been well-established as intermediates for the construction of N -containing 5- and 6-membered heterocycles including indoles and pyridines 1621 . Iminyl radical is normally generated from N-O bond cleavage using either light or initiators (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Phenanthridine and its structurally related compounds play essential roles in a variety of chemical fields due to their existence in a broad range of natural products, bioactive compounds, and functional materials ( Figure 1) [1][2][3][4][5]. Phenanthridine was first synthesized from the reaction between benzaldehyde and aniline in 1889 [6], and a number of preparative methods have been reported to date [1,[7][8][9]. However, since most protocols necessitate harsh reaction conditions and/or multi-step reaction sequences from commercially available starting materials [10,11], concise and mild preparation procedures for this important class of compounds are still in high demand [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%